Numerical Simulation of Stresses Produced on Hydraulic Clutch Discs Due to Heat Generated During Operation - Jairo Martins (Pouyan Press, 2021)
Modern clutches are a critical component of a machine/equipment because they are designed to transfer and control torque, consequently producing movements, enabling safe operation, and controlling movement when necessary. When a clutch engages it transfers torque and allows a machine to produce mechanical work as a final result. The clutch engagement process generates heat due to the slipping of clutch discs. Although pressure applied on clutch discs generates stresses in the disc material, it was not clear how severe a combination of pressure and heat might raise the stresses. This study aimed to produce a numerical simulation to determine the impact of temperature also torque changes in the clutch discs when it transfers movement. Some static and thermal numerical simulations by Finite Element Analysis (FEA) (linear-elastic analysis) were performed, which considered two scenarios; (1) first with only pressures applied on clutch disc's face; (2) where heat was added to pressures. These mathematical simulations revealed that discs stresses are highly sensitive to thermal variations since for some cases the maximum von Mises stresses exceeded discs material mechanical strength leading it to failure. To overcome this problem it is compulsory to consider heat when designing a clutch and a cooling system for it.